Evaluation of graded levels of corn fermented protein on extrusion processing and diet utilization in healthy adult dogs - Kilburn-Kappeler, Logan R.; Aldrich, Charles G. (Frontiers in Animal Science, 2023)
There has been increased interest among pet owners to feed vegetarian diets to their pets. However, the primary protein sources used in pet food today are animal based, warranting a need to evaluate novel plant-based ingredients to meet the protein demand. Corn fermented protein (CFP), a coproduct from ethanol production, may provide a plant-based alternative protein source for pet food. Therefore, the objectives of this study were to determine the effects of increasing levels of CFP on extrusion processing, stool quality, apparent total tract digestibility, and palatability in dog diets. Four extruded diets were fed to 12 adult beagle dogs in a replicated 4 × 4 Latin square design. The control diet contained 15% soybean meal (0C) and CFP was exchanged at either 5%, 10%, or 15% of soybean meal (5C, 10C, and 15C, respectively). Dogs were fed each dietary treatment for 9 days of adaption followed by 5 days of total fecal collection. Feces were scored on a 1–5 scale, with 1 representing liquid diarrhea and 5 representing hard pellet-like. Titanium dioxide (0.4%) was added to all diets as an external marker to estimate digestibility. Data were analyzed using orthogonal contrasts in SAS (version 9.4; SAS Institute, Inc., Cary, NC, USA). Dry bulk density of kibble decreased (P < 0.05), whereas kibble toughness increased (P < 0.05) with CFP inclusion. Fecal dry matter, dry fecal output, and defecations per day increased (P < 0.05) when dogs were fed increased levels of CFP. Dry matter and crude protein digestibility of CFP treatments were comparable (P > 0.05) to 0C. There was a decrease (P < 0.05) in organic matter, crude fat, gross energy, and total dietary fiber digestibility in the CFP treatments compared with 0C. A cubic relationship (P < 0.05) was observed in the digestibility of all nutrients except crude fat, indicating that 10C resulted in the lowest digestibility. For the palatability assessment, dogs had no preference when comparing the 5C treatment with the 0C treatment. Even with the differences in dietary treatments, inclusion of CFP at 5%, 10%, and 15% still resulted in acceptable processing parameters, kibble characteristics, and utilization when fed to dogs.